Pengaruh Budaya Perusahan, Motivasi, Dan Keselamatan Kerja Terhadap Kinerja Karyawan - Wakano, Margareth Agustina (JURNAL RISET BISNIS DAN MANAJEMEN, 2014)
The purpose of this study was to determine the influence of corporate culture, motivation, and safety of the employee's performance. research instrument used was a questionnaire form of a structured questionnaire. The questionnaire used is enclosed questionnaire is a model that has been available answer questions, so respondents simply choose alternative answers according to the opinion or choice. The closed questions respondents to explain the variable corporate culture, motivation, workplace safety, and employee performance. results of studies using multiple regression analysis showed that partially proves corporate culture, motivation, and affect the safety performance of employees at PT. Antam Tbk. Buli. Suggested to the company to always give you a raise, develop employee skills and abilities in order to further enhance employee performance and profitable for the company. Keywords: transfer, promotion, career development employee